Exploring the Impact of Automation on the Future of Work in the Agriculture Sector in Indonesia - Rifki Maulana Iqbal Taufik; Tri Kurnia Revul Andina (Journal of Social Studies, 2025)
This research aims to examine the impact of automation on future work in Indonesia's agriculture sector. Internet and digital platforms have altered many aspects of life and resulted in automation in several fields, including agriculture. The emergence of new technologies is often perceived as a threat and a challenge for this sector and its workers. Using a desk study method, however, the result shows that the automation of agriculture is beneficial to Indonesia's economy. This is not only in terms of gross domestic product (GDP) but also in terms of enhancing the quality of smallholder employment and the interest of youth in working in this sector. Farmers' use of the internet and smartphones have become catalysts in adopting automation in the present and emerging. Digital technology has become an important intermediate factor that helps farmers improve their productivity. This has become the mainstream of the adoption of the technology in agriculture rather than mechanization. Job replacement due to automation will possibly not happen in Indonesia due to labour market conditions, disparity of land ownership, and the high cost of implementing automation. Furthermore, this research addresses aspects that deserve attention, including job quality, social protection, industrial relations, inequality, gender, and participation.